Engaging fringe stakeholders in business and society research: applying visual participatory research methods - McCarthy, Lauren; Muthuri, J. (Sage, 2018)
Business and society (B&S) researchers, as well as practitioners, have been critiqued for ignoring those with less voice and power (e.g. women, non-literate or indigenous peoples) often referred to as ‘fringe stakeholders’. Existing methods used in B&S research often fail to address issues of meaningful participation, voice and power, especially in developing countries. In this article we stress the utility of visual participatory research (VPR) methods in B&S research to fill this gap. Through a case study on engaging Ghanaian cocoa farmers on gender inequality issues we explore how VPR methods may be used by researchers to achieve more inclusive, and thus more credible, stakeholder research that can improve decision-making within businesses. Furthermore, we argue that ingrained social and environmental problems tackled by B&S research and the unique context in which they occur may open up new opportunities to develop participatory visual methods for social change.